Technical and Institutional Evaluation of Selected National and Communal Irrigation Systems and Characterization of Irrigation Sector Governance Structure: Integrative Chapter. Final Report - Arlene B. Inocencio; Carl Ureta; Alex Baulita; Arman Baulita; Roberto Clemente; Roger Luyun; Dulce Elazegui (Philippine Institute for Development Studies (PIDS), 2016)
This discussion paper presents an analysis of the performance of national (NIS) and communal irrigation systems (CIS) by region, complemented by technical and institutional assessments of 30 sample NIS and 66 sample CIS in Luzon. It shows that there is value in looking at subnational trends. Using secondary data from the central and regional offices of the National Irrigation Administration (NIA) and the systems, complemented by key informant interviews and ocular inspections, this study establishes key institutional and technical constraints to improving the performance of NIS and CIS systems. In addition to the selected key performance indicators, some ratios are used to characterize the capacities of the systems in terms of manpower, level of functionality, financial structure, and productivity of the systems. This study examines the NIS cases by province, size (large, medium, small), technology (gravity type vs pump type), location (upstream, midstream, downstream), vintage (pre-NIA, 1965-1980, 1981-2013), and by some measures of "success", and presents a number of instructive results.
Keywords: 330; irrigation performance; management and development of irrigation systems; irrigators'association; Luzon